ANALISIS SISTEM AKUNTANSI PERSEDIAAN BAHAN BAKU PADA PT. BUMI MEKAR TANI KECAMATAN NIBUNG - Subianto Subianto; Fitri Anggraini (LPPM Universitas Bina Insan, 2020)
The purpose of this study is to see the implementation of the accounting system toward raw material in PT. Bumi MekarTani Nibung district. This study uses a qualitative descriptive research design. Data used in the form of documentation and interviews. The analysis technique used is descriptive method. The results of the analysis showed that the raw material inventory accounting system at PT. Bumi Mekar Tani hadbeen running well even though the company applied its own system and procedures. The obstacle did by the company was the lack of coordination and cooperation between the administration and the sorting division. A solution to overcome these obstacles was by coordinating and adjusting the procedures.